Archaisms in Abay’s Writing - Kurmanbaiuly, Ш.; Adilov, М.Е. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2020)
In this article, we have analyzed individual archaisms of Abay, which are almost out of active use. The presented archaisms are not used in the modern literary language. We can only find them in phraseological units, Proverbs, and paired words. As a result of research, it turned out that some archaisms have undergone semantic meaning and require specific clarifications. To parse these words, you need to refer to the materials of related languages. In this work, we have tried to analyze and give meaning to some archaism of the great poet Abay’s poetry using materials from the Turkic and Mongolian languages.